Natural Coagulant Efficiency of Moringa Oleifera Seeds in Raw Water Treatment - Hassan, Ahmad Benwan; Hasan, Manar Banwan; Shadhar, Mohanad Hatem; Al-Kanany, Nawar Banwan Hassan (Z͡H︡urnal inz͡h︡enernykh nauk, 2025)
Adverse health and environmental impacts of conventional chemical compounds in treating water and wastewater encouraged the study of natural alternatives, especially plant-based compounds. This study aims to investigate the feasibility of Moringa oleifera (MO) seeds as an eco-friendly natural coagulant and to compare their effectiveness with the chemical coagulant – aluminum sulfate (Alum). The performance of MO in turbidity and chemical oxygen demand (COD) removal from raw water employing the jar test was examined. Coagulation conditions were optimized using a jar test to determine the optimum dose of MO and pH level. The impact of the MO on treated water characteristics (electrical conductivity, pH, and total dissolved solids) was also examined. The experiment used a range of MO doses (50, 100, 150, 200, and 300 mg/l) and Alum (5, 10, 20, 30, and 40 mg/l) to treat raw water samples. The performance of both coagulants followed similar trends. The maximum turbidity removal efficiency was about 97 % obtained at an optimum dosage of 100 mg/l of MO, while for COD, the highest removal was about 49 % at 150 mg/l of MO. No significant effect of MO dosing on the pH level of the solution was noticed, while a substantial increase in electrical conductivity from 591 ± 1.5 μS/cm to 620 ± 1.5 μS/cm was observed when the dosage of MO increased to 300 mg/l. Total dissolved solids (TDS) also increased for raw water from 255 ± 1.0 μS/cm to 367 ± 2.0 μS/cm at a 300 mg/l dosage. One-way analysis of variance for the relation between dose and turbidity removal shows that the model is significant (F-value of 76.1, P-value less than 0.0001).